THE LESS-INTERRESTED OF ISLAMIC BANK FOR ISSUING SUKUK: Factors and Recommendations - Awaludin, Taufik; Syauqi Beik, Irfan; Ismal, Rifki (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2016)
This study attempts to identify dominant factors for banks to issue sukuk and emission features. Applying interviews and Analytic Network Process, this paper Found that the sub-elements which are dominant in influencing IB less interested in issuing sukuk, namely: averse selection/amount cost of fund (management), investment rating companies (investor), the results of using sukuk funds (regulation) and profitability condition (finance). Meanwhile, the sub-elements which are dominant in determining the features of the issuance of sukuk are: macroeconomic condition (emission values), expectations of investors (return)), the contract and the structure of sukuk (collateral), managing mismatch (period), and company liquidity (payment term).  The method used in this reseach is the Analytic Network Process (ANP). This study will identify the aspects of emission factors and features.***Penelitian ini bertujuan untuk melakukan identifikasi faktor-faktor dominan dalam persoalan sukuk dan ciri-ciri pengeluarannya. Menerapkan teknik wawancara dan proses jejaring analitis, makalah ini menemukan bahwa sub-sub elemen yang dominan mempengaruhi kurang menariknya IB dalam persoalan sukuk, adalah: menolak seleksi/jumlah pembiayaan (manajemen), rating investasi perusahaan (investor), hasil-hasil penerapan pembiayaan sukuk (regulasi) dan kondisi profitabilitas (keuangan). Sementara itu, sub-sub elemen yang dominan dalam menentukan ciri-ciri pengeluaran sukuk adalah: kondisi makro ekonomi (nilai pengeluaran), ekspektasi dari investor (keuntungan), kontrak dan struktur sukuk (jaminan), pengelolaan yang tidak sebanding (waktu) dan likuiditas perusahaan (syarat-syarat pembayaran). Metode yang digunakan dalam penelitian ini adalah Analytic Network Process (ANP). Penelitian ini akan mengidentifikasi aspek faktor emisi dan fitur. ANP adalah teori matematika dalam pengambilan keputusan yang mampu menganalisis pengaruh melalui asumsi untuk memecahkan berbagai masalah.